EFEKTIVITAS PENGGUNAAN MODEL PEMBELAJARAN DISCOVERY LEARNING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA DI SMP NEGERI 5 PADANGSIDIMPUAN - Ester Simare-Mare; Sinar Depi Harahap; Nunik Ardiana (JURNAL MathEdu (Mathematic Education Journal), 2020)
The aim of this study was to know whether using discovery learning model was effective on students’ mathematical problem solving ability on the topic of beam at the eighth grade students of SMP Negeri 5 Padangsidimpuan. The research was conducted by applying experimental method (one group pretest post test design) with 27 students as the sample and they were taken by using simple random sampling technique from 258 students. Observation and test were used in collecting the data. Based on descriptive analysis, it was found: (a) the average of using discovery learning model was 3.84 (very good category) and (b) the average of students’ mathematical problem solving ability on the topic beam before using discovery learning model was 63.33 (enough category) and after using discovery learning model was 83.67 ( very good category).Furthermore, based on inferential statistic by using pair sample ttest, (SPSS version 17), the result showed the significant value was less than 0.05 (0.000<0.05). It means, discovery learning model was effective used on students’ mathematical problem solving ability on the topic beam at the eighth grade students of SP Negeri 5 Padangsidimpuan.